(untitled) (Studia austriaca, 2012)
The essay’s introduction examines the importance of Italy for Josef Winkler and puts the novella «Natura morta» in context with his oeuvre. The subsequent analysis of the text highlights the technique used by the author, which shows similarities with the process of film shooting. The narrator’s eye follows the main character like a movie camera and is focused on numerous details as if it were zooming on them. In this process, while advancing the novella’s plot, the author paints a colorful portrait of Rome, bringing the city to life like a baroque still life.